A praça e a cidade : o caso de Paranavaí-PR - Freire, Rose Hélida Astolfo (2012)
The study aimed to analyze qualitative and quantitatively, twenty-five squares located in urban area in Paranavaí / PR, verifying the importance of these spaces to the city, from analyzes based on factors such as type, insertion into the urban area, equipment and / or structures, vegetation, location and surroundings. For this, was used the methodology proposed by De Angelis (2000), which has two types of survey, a qualitative and a quantitative, developed from the application forms analyzed in each square. We tried also to raise the accessibility conditions on such thoroughfares, aimed at people with special needs (PSN), as well as information on laws creating these parks and toponyms. As a result it was found that the maintaining of these spaces need to be reviewed, because some equipment such as benches, bins, floor concepts were predominantly poor and fair, depending on its condition, functionality and / or location. On the issue of accessibility, it is noted that in the squares of Paranavaí there are lacking in ways that promote access to PSN, because only 23% have access ramps that obey the accessibility standards established under of 10% have tactile floor, only 4 % have special parking and there are no toilets and public telephones adapted for PSN. The concentration of trees belonging to the same species was observed like another negative factor of Paranavaí squares, and only two species (Caesalpinia peltophoroides - sibipiruna; Tabebuia avellanedae - purple-ipe) represent 71.7% of the afforestation of squares. Thus, through this work, we tried to point out relevant aspects that need to be reviewed and discussed, to support improvements in the policy of management of these parks, and so fulfill effectively the role of public spaces facing to socialization and recreation.